Intradural fat graft packing is not indispensable in preventing postoperative cerebrospinal fluid leakage in endoscopic endonasal pituitary adenoma surgeries - Wang, Xiefeng; Wang, Binbin; Cheng, Gang; You, Yongping; Tao, Chao (Frontiers in Oncology, 2023)
Is intradural fat graft packing indispensable in preventing postoperative cerebrospinal fluid leakage in endoscopic endonasal pituitary adenoma surgeries? To review the methods and outcomes of our graded sellar floor reconstruction strategy without fat graft packing in endoscopic endonasal pituitary adenoma surgeries. Methods From March 2018 to December 2022, 200 patients underwent endoscopic endonasal pituitary adenoma resection by a single author in our institute. We applied different graded skull base reconstruction strategies in different periods. Intradural fat graft packing was used to reconstruct the skull base in the early period, from March 2018 to June 2019, but fat graft was not used in the late period, from January 2020 to December 2022. The effect of these different graded skull base reconstruction 删除了: Fat strategies and whether intradural fat graft packing is necessary was evaluated by observing the incidence of postoperative cerebrospinal fluid leak.In the early period, fat graft was used to reconstruct skull base when the intraoperative CSF leakage existed. There were 2 patients suffered from postoperative cerebrospinal fluid leak in this group. In the late period, fat graft was not used to reconstruct the skull base, and no patient suffered from postoperative cerebrospinal fluid leakage in this group.Intradural fat graft packing is unnecessary in the endoscopic endonasal pituitary adenoma resection. The outcome of our graded sellar floor reconstruction strategy is satisfactory.